Improved glycaemic control and weight benefit with iGlarLixi versus insulin glargine 100 U/mL in Chinese people with type 2 diabetes advancing their therapy from basal insulin plus oral antihyperglycaemic drugs: Results from the LixiLan‐L‐CN randomized controlled trial. Issue 11 (25th July 2022) - Yuan, Xiaoyong; Guo, Xiaohui; Zhang, Junqing; Dong, Xiaolin; Lu, Yibing; Pang, Wuyan; Gu, Shenghong; Niemoeller, Elisabeth; Ping, Lin; Nian, Gaowei; Souhami, Elisabeth; ,
Abstract: Aims: To evaluate the efficacy and safety of iGlarLixi compared with iGlar in Chinese adults with type 2 diabetes advancing therapy from basal insulin ± oral antihyperglycaemic drugs. Materials and methods: LixiLan‐L‐CN (NCT03798080) was a 30‐week randomized, active‐controlled, open‐label, parallel‐group, multicentre study. Participants were randomized 1:1 to iGlarLixi or iGlar. The primary objective was to show the superiority of iGlarLixi over iGlar in glycated haemoglobin (HbA1c) change from baseline to Week 30. Results: In total, 426 participants were randomized to iGlarLixi (n = 212) or iGlar (n = 214). Mean age was 58 years, 67% had a body mass index ≥24 kg/m 2, corresponding to overweight/obesity, and the mean diabetes duration was 12.3 years. From mean baseline HbA1c of 8.1% in both groups, greater decreases were seen with iGlarLixi versus iGlar [least squares mean difference: −0.7 (95% confidence interval: −0.9, −0.6)%; p < .0001] to final HbA1c of 6.7% and 7.4%, respectively. HbA1c <7.0% achievement was greater with iGlarLixi (63.3%) versus iGlar (29.9%; p < .0001). Mean body weight decreased with iGlarLixi and increased with iGlar [least squares mean difference: −0.9 (95% confidence interval: −1.4, −0.5) kg; p = .0001]. Hypoglycaemia incidence was similar between groups. Few gastrointestinal adverse events occurred (rated mild/moderate) with a slightly higher incidence with iGlarLixi than iGlar. Conclusions: iGlarLixi provided better glycaemic control and facilitated more participants to reach glycaemic targets alongside beneficial effects on body weight, no additional risk of hypoglycaemia, and few gastrointestinal AEs, supporting iGlarLixi use as an efficacious and well tolerated therapy option in Chinese people with long‐standing T2D advancing therapy from basal insulin.